(untitled) (Medical Forum Monthly, 2024)
Objective: The aim of this study is to see the frequency of vitamin D and its impact on the sample population. Study Design: Descriptive / cross sectional study Place and Duration of Study: This study was conducted at Trauma and General Hospital, Karachi from January 2014 to June 2015. Materials and Methods: 205 patients were included in the study. Participants were assessed according to predesigned questionnaire. All patients were subjected to have complete blood count, serum calcium, phosphorous, albumin, alkaline phosphatase, SGPT, vitamin D and parathyroid hormone levels along with X-rays of hip joint and femur. Results: Out of total 205 patients, 12.7% were males and 87.3% were females. Mean age was 41.32±15.225 years. 5.9% had normal levels of Vitamin D3, while 60.5%, 27% and 6.5% showed mild, moderate and severe deficiency. Serum calcium and phosphorous were deficient in 20.4% and 31.9% respectively. Serum alkaline phosphatase and parathyroid hormone were normal in most of the participants. The deficiency of Vitamin D3 was mostly due to reduced sun exposure and excessive clothing (86.8%) while 8.3% showed malabsorption. This deficiency caused bone pains, and muscle pains in 55.6%, and 17.6% respectively. But none of the patient had any fracture. Conclusion: Levels of Vitamin D3 are low in most of the people of Karachi but without any gross deformity. It is advisable to readdress the daily requirement of vitamin D bring the awareness among people regarding sun exposure and daily use of vitamin D supplements.